Bacterial and host interactions in Staphylococcus aureus-induced septic arthritis—understanding pathogenesis and exploring therapeutic strategies - Hu, Zhicheng; Engdahl, Cecilia; Pullerits, Rille; Mohammad, Majd; Jin, Tao (Frontiers in Microbiology, 2025)
Septic arthritis is a severe and rapidly destructive joint infection, primarily caused by Staphylococcus aureus. The interplay between bacterial virulence factors and host immune responses determines disease progression and clinical outcomes. This review discusses the key bacterial factors that contribute to septic arthritis, including S. aureus cell wall components, surface proteins, and secreted toxins. In parallel, host-related factors, such as aging, immune responses, and genetic predispositions, are examined in conjunction with the impact of S. aureus infection on bone integrity and osteoimmunological mechanisms. Finally, this review highlights emerging therapeutic approaches, including targeted anti-virulence strategies, immune modulation, and anti-osteoclastogenic interventions, in mitigating joint damage. Understanding the multifaceted interactions between S. aureus and the host immune system is crucial for advancing treatment strategies and reducing morbidity associated with septic arthritis.